Ta’arudhal-Adillah: Metode Memahami Dalil dalam Penyelesaian Persoalan Hukum - Muhammad Mulyadi; Raisya Aurora A; Rihan Dwi Putri; Kurniati Kurniati (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2024)
This research aims to delve into the method of ta’arudhal-adillah in understanding legal evidence for resolving legal issues within the context of Islamic law. A qualitative approach is employed using library research, facilitating an in-depth analysis of relevant Islamic legal literature. The primary findings indicate that the principles of al-jam'u wa al-taufiq, which combine various evidences to reach holistic conclusions, and the concept of nasakh, which addresses the abrogation or alteration of laws based on newer evidences, are pivotal in understanding the interaction and hierarchy of legal evidences. This study provides profound insights into how legal evidences influence each other and are applied in contemporary Islamic legal practice, highlighting their relevance in meeting the legal needs of modern societies.